Pemamfaatan Produk Hasil Samping Ikan Baji - Baji (Grammoplites scaber) Sebagai Tepung Yang Bergizi Berbasis “Zero Waste Concept” - Ayu Diana; Muhammad Zakiyul Fikri (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
The processing of Grammoplites scaber as a whole by utilizing the processed products will provide more benefits such as reducing waste management activities. The research objective is to increase the potential of baji-baji fish by conducting continuous studies through the use of byproducts as flour against its nutritional content, as well as optimally utilizing it through zero waste concept. The research method used was an experimental method and experimental design in the form of a not factorial complete random design in 3 treatments (head, stomach contents, skin). The principle of zero waste concept by handling waste byproducts by utilizing optimally and yield becomes a parameter in the most important thing to know the economic value and effectiveness of a product process. Based on the test results it is known that the percentage of baji-baji fishes for waste byproducts is 76% compared to meat 24%, the largest byproducts are found in the head bones (47%) and skin (18%) and stomach contents in the body (11% ). Yields on flour making are Head (71%), stomach contents (9%), and skin (20%). The best chemical composition of flour is Protein 65,377% (head flour), water content 4,509% (skin flour), fat 13,463% (skin flour), ash content 2,204% (head flour), and carbohydrates 22,208% (stomach contents). Therefore the 76% baji-baji fish by-product can be used as raw material for making flour and has a good nutritional content.